(untitled) (Journal of actual problems of jurisprudence, 2018)
Modern economic development of economic relations, national economic states, the desire of creating a comprehensive free-trade areas have brought to what is necessary to create new international agreements on the exchange of goods and services, to promote financial resources. A special role in the system of state administration of foreign economic activity refers to the customs service, in a timely and quality service to participants of foreign economic activity of other countries. Key words: сustoms regulation, administration, EurAsEC, economic.